2010
DOI: 10.1002/ibd.21072
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-macrophage colony-stimulating factor elicits bone marrow-derived cells that promote efficient colonic mucosal healing

Abstract: Our study shows that GM-CSF-dependent stimulation of bone marrow-derived cells during DSS-induced colitis accelerates colonic tissue repair. These data provide a putative mechanism for the observed beneficial effects of GM-CSF therapy in Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
83
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 48 publications
3
83
0
Order By: Relevance
“…GM-CSF has been shown to reduce DSS-induced colitis and decrease the levels of pro-inflammatory cytokines (TNF-and IL-1 ) in colonic tissue samples [295,296]. These results were confirmed recently; GM-CSF decreased the DSS-induced colitis and the expression of pro-inflammatory cytokines.…”
Section: Immune Stimulationsupporting
confidence: 53%
See 1 more Smart Citation
“…GM-CSF has been shown to reduce DSS-induced colitis and decrease the levels of pro-inflammatory cytokines (TNF-and IL-1 ) in colonic tissue samples [295,296]. These results were confirmed recently; GM-CSF decreased the DSS-induced colitis and the expression of pro-inflammatory cytokines.…”
Section: Immune Stimulationsupporting
confidence: 53%
“…These results were confirmed recently; GM-CSF decreased the DSS-induced colitis and the expression of pro-inflammatory cytokines. In addition, the duration of ulcer healing was shorter and epithelial regeneration was facilitated in GM-CSF-treated mice [295]. Based on these preclinical results, a potential role for GM-CSF in the therapy of patients with IBD has been raised.…”
Section: Immune Stimulationmentioning
confidence: 99%
“…Previous studies of chemically induced colitis in rats revealed that depletion or adhesion blockade of neutrophils aggravated the intestinal histopathology, and promotion of bone marrow-derived granulocyte differentiation facilitated the mucosal repair processes. 28,55,56 One report indicates that neutrophil-derived IL-1b is involved in promoting epithelial restitution and mucosal wound healing after ischemic challenge via a cyclooxygenase-2-dependent mechanism. 57 Previous studies showed that adaptive hypoxia protects the intestinal epithelial barrier integrity via transcriptional regulation of hypoxiainducible factor 1.…”
Section: Discussionmentioning
confidence: 99%
“…These antibodies are directed against GM-CSF which is a cytokine that is necessary for anti-microbial functions of myeloid cells and that have an important role in the regulation of intestinal mucosal damage, in intestinal immunity and inflammatory responses [10][11][12][13][14]. Mice deficient in GM-CSF had defects in mucosal barrier function with more severe intestinal and systemic infection after enteric infection, more severe colitis after enteric exposure to dextran sodium sulphate or developed transmural ileitis following non-steroidal anti-inflammatory drug (NSAID) exposure [10][11][12][13][14]. GM-CSF therapy improved mucosal repair and could have a role in clinical improvement in CD [10][11][12][13]15].…”
mentioning
confidence: 99%
“…Mice deficient in GM-CSF had defects in mucosal barrier function with more severe intestinal and systemic infection after enteric infection, more severe colitis after enteric exposure to dextran sodium sulphate or developed transmural ileitis following non-steroidal anti-inflammatory drug (NSAID) exposure [10][11][12][13][14]. GM-CSF therapy improved mucosal repair and could have a role in clinical improvement in CD [10][11][12][13]15]. Jurickova et al found that anti-GM-CSF Ab were produced by lamina propria mononuclear cells isolated from CD ileal resection specimens and that peripheral blood contains GM-CSF neutralizing capacity [16].…”
mentioning
confidence: 99%